dirāsāt fī nuṣūṣ mismāriyyah ġair manšūrah min minṭagah diyālā ḥawḍ ḥamrīn, tall ḥadād - Muḥammad, ’Aḥmad Kāmil
Studies in Unpublished Cuneiform Texts from Diyala Region — Himrin Basin, Tell Haddad; M.A. Thesis. College of Arts. Baghdad University. Chief Supervisor: Farouk Nasir al-Rawi; includes autograph copies of 25 OB tablets and two tablet cases; autograph copies of the legends of 44 seal impressions; 17 photos of tablet faces or edges (one pictorial seal impression, ḥadād 586), two sketch maps, one map indicating find spots of tablets.